Research on thermal runaway process of 18650 cylindrical lithium-ion batteries with different cathodes using cone calorimetry. (1st August 2023) - Liu, Changcheng; Shen, Wanyu; Liu, Xiaozhao; Chen, Yanjun; Ding, Chao; Huang, Que
Abstract: The complex chemical reactions and the safety properties of lithium-ion batteries (LIBs) with different cathode materials are various from each other. In this article, a cone calorimeter was used to measure the mass change, heat generation and gas release characteristics of three types of 18650 cylindrical LIBs with lithium iron phosphate (LFP), lithium cobalt oxide (LCO) or lithium nickel manganese cobalt oxide (NMC) as the positive electrode material. All samples were tested under 9 kinds of conditions combined state of charge (SOC) of 33 %, 66 %, 100 % with heat flux of 30 kW/m 2, 45 kW/m 2, 60 kW/m 2, respectively. Especially, the principal component analysis (PCA) method was applied to further analyze the difference of thermal runaway (TR) behavior for the three kinds of batteries. Moreover, the influence of SOC and heat flux on the safety features of 18650-cylinder LIBs was analyzed. After comparing parameters such as mass loss rate (MLR), gas generation/consumption, heat release, toxicity among the tested 18650 cylindrical LIBs, the results displayed that the influence of external heat flux on the intensity of battery TR reactions was lower than that of SOC. The TR risk of LCO and NMC batteries with relatively high SOC was higher than that of LFP ones in large fire scenarios. When the fire scale was relatively small, the main factor that determined the risk of battery fire was the type of cathode, while which became SOC under the opposite situation of large-scale fire. PCA results showed that LFP and NMC batteries presented almost completely different TR characteristics, which could provide important references for battery design, corresponding fire investigation and attack. Highlights: With high state of charge, LiFePO4 was safer than LiCoO2 and Li1-n [Nix Mny Coz ]O2 under external heat flux of 60 kW/m 2 . Under 30 kW/m 2, the critical factor that influenced the battery fire risk was the type of cathode. Under 60 kW/m 2, the key factor which determined the cell thermal hazard was the state of charge. Principal component analysis was applied to evaluate the weight of impact factors on battery safety. Principal component analysis results indicated that various batteries showed different distribution.